Base Period, Qualifying Period and the Equilibrium Rate of Unemployment - Elke J. Jahn; Thomas Wagner (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2006)
Unemployment benefits, benefit duration, base period and qualifying period are constituent parameters of the unemployment insurance system in most OECD countries. From economic research we know that the amount and duration of unemployment benefits increase unemployment. To analyze the effects of the other two parameters we use a matching model with search frictions and show that there is a trade-off between the qualifying and the base period on the one hand and the amount and duration of the unemployment benefits on the other. A country that combines a high level of unemployment benefits with a long benefit duration can neutralize the effect on the equilibrium rate of unemployment with a long qualifying and/or a short base period. – – Lohnersatzleistungen, Anspruchsdauern, Rahmenfristen und Anwartschaftszeiten sind konstituierende Parameter der Arbeitslosenversicherungen in den meisten OECD Ländern. Ökonomische Untersuchungen zeigen, dass Höhe und Dauer der Lohnersatzleistungen die Arbeitslosigkeit erhöhen. Im Rahmen eines Matching-Modells untersuchen wir die Wirkung der anderen beiden Parameter und zeigen, dass ein trade-off zwischen der Anwartschaftszeit und der Rahmenfrist auf der einen und der Höhe und der Dauer der Lohnersatzleistungen auf der anderen Seite existiert. Ein Land mit einer hohen Arbeitslosenunterstützung und langer Anspruchsdauer kann die Wirkung auf die Arbeitslosenquote durch eine lange Anwartschaftszeit und eine kurze Rahmenfrist neutralisieren.
Keywords: J41; J68; J64; 330; Unemployment insurance; base period; qualifying period